Digital Literacy Strengthens Character Education in the Era of Society 5.0 - Nurdiansyah, Urai; Wahab, Wahab (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2025)
Digital literacy plays an important role in character education in Society 5.0, where advances in digital technology require individuals to have the ability to use, evaluate and actively participate in digital environments. As the key to developing moral and ethical values, digital literacy supports learners' character building through technological knowledge, digital skills, responsible behavior in online media, and ethical awareness. Digital literacy can encourage the growth of these values including honesty, accountability, empathy, cooperation, and problem-solving skills. Finally, digital literacy teaches students about the social, economic and cultural consequences of their actions online. Therefore, collaboration between various parties is needed to enable efficient integration of digital literacy into character education in the Era of Society 5.0.